Work-associated irritable larynx syndrome. Issue 2 (April 2015) - Anderson, Jennifer A.
Abstract : Purpose of review: The purpose of this study is to review the relevant literature concerning work-associated irritable larynx syndrome (WILS), a hyperkinetic laryngeal disorder associated with occupational irritant exposure. Clinical symptoms are variable and include dysphonia, cough, dyspnoea and globus pharyngeus. WILS is a clinical diagnosis and can be difficult to differentiate from asthma. Treatment options for WILS include medical and behavioural therapy. Recent findings: Laryngeal-centred upper airway symptoms secondary to airborne irritants have been documented in the literature under a variety of diagnostic labels, including WILS, vocal cord dysfunction (VCD), laryngeal hypersensitivity and laryngeal neuropathy and many others. The underlying pathophysiology is as yet poorly understood; however, the clinical scenario suggests a multifactorial nature to the disorder. More recent literature indicates that central neuronal plasticity, inflammatory processes and psychological factors are all likely contributors. Summary: Possible mechanisms for WILS include central neuronal network plasticity after noxious exposure and/or viral infection, inflammation (i.e. reflux disease) and intrinsic patient factors such a psychological state. Treatment is individualized and frequently includes one or more of the following: environmental changes in the workplace, GERD therapy, behavioural/speech therapy, psychotherapy counselling and neural modifiers.